Development of Square and Triangle Surface Area Pocket Books as Learning Media for Junior High Schools - F Fajriana; M Mursalin; Atikah Fitriani (SAINTIS Publishing, 2022)
This study was conducted at SMP Negeri 8 Lhokseumawe about the development of rectangular and triangular pocket books against the background of the lack of availability of textbooks in schools, coupled with inadequate learning media that supports students to study independently, thus causing low learning motivation of students. and learning outcomes have not increased. The aims of this study: (1) To determine the validity of the development of rectangular and triangular surface area pocket books as learning media for junior high schools, (2) to determine the feasibility of developing square and triangular surface area pocket books as learning media for junior high schools, (3) to find out responses teachers and students on the development of rectangular and triangular surface area pocket books as learning media for junior high schools. The design of this research is research and development called Research and Development (R D) using the Borg and Gall model modified into 7 stages according to Sugiyono. Data collection techniques using validation sheets and questionnaires. The results obtained from the validation of media experts obtained a percentage of 91.48% and material experts obtained a percentage of 83.52% with a very valid category. The results of the feasibility of pocket books obtained a percentage of 84.69% with a very decent category, and teacher responses to pocket books obtained a percentage of 89.52% in a very good category, and students' responses to pocket books obtained a percentage of 80% in a good category. So it can be concluded that pocket books can be well received at SMP Negeri 8 Lhokseumawe. Recommendations from the research are expected to schools, institutions related to educational practitioners to conduct trials on a broad group so that the level of effectiveness can be known to support learning.